1999
DOI: 10.1159/000015386
|View full text |Cite
|
Sign up to set email alerts
|

Comparative FISH mapping on Z chromosomes of chicken and Japanese quail

Abstract: Using direct R-banding fluorescence in situ hybridization, we assigned five functional genes—growth hormone receptor (GHR), prolactin receptor (PRLR), spleen tyrosine kinase (SYK), aldolase B (ALDOB), and muscle skeletal receptor tyrosine kinase (MUSK)—to the chicken Z chromosome. SYK and MUSK were newly localized to the chicken Z chromosome in this study. GHR and PRLR were situated close to each other on the short arm of the chicken Z chromosome, as are their counterparts on human chromosome 5. SYK, MUSK, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
5
19
0
Order By: Relevance
“…Hybridization of the same probe also exhibited specific and unambiguous FITC signals on the long arm of the Z chromosome of Japanese quail (Fig. 1b) which confirms the data obtained using the chicken cDNA probe (Suzuki et al, 1999). In order to obtain effective hybridization in pheasant and duck for the heterologous, chicken-derived probe, post-hybridization washing was conducted by lowering the stringency (washing in 2× SSC at 39°C).…”
Section: Resultssupporting
confidence: 81%
“…Hybridization of the same probe also exhibited specific and unambiguous FITC signals on the long arm of the Z chromosome of Japanese quail (Fig. 1b) which confirms the data obtained using the chicken cDNA probe (Suzuki et al, 1999). In order to obtain effective hybridization in pheasant and duck for the heterologous, chicken-derived probe, post-hybridization washing was conducted by lowering the stringency (washing in 2× SSC at 39°C).…”
Section: Resultssupporting
confidence: 81%
“…By BLAST analysis, the locations of all 12 genes in the chromosomes were made clear, which was consistent with the original mapping results of some genes [10,16,32,34,42].…”
Section: Locating Genes On Chromosomessupporting
confidence: 84%
“…Although the structure of the Z chromosome varies considerably among avian species, its gene content has been evolutionarily conserved. Comparative gene mapping Ogawa et al, 1998;Suzuki et al, 1999) including DMRT1 and Zoo-FISH experiments (Ambady et al, 1997;Shetty et al, 1999) in primitive and higher birds suggested an extreme stability of the Z chromosome, which is reminiscent of the mammalian X chromosome. Despite the occurrence of evolutionary chromosome rearrangements, linkage groups on the ancestral Z did not break up and were not relocated on different autosomes.…”
Section: Discussionmentioning
confidence: 99%